The sword of the silver knight - Warner, Gertrude Chandler, 1890- (Morton Grove, Ill. : Albert Whitman, 2005)
The Aldens help out at a medieval fair and try to find a valuable sword which has been stolen from the fair.
3.
007-012.
Keywords: Brothers and sisters -- Fiction; Fairs -- Fiction; Swords -- Fiction; Orphans -- Fiction; Mystery and detective stories